Do political connections stifle firm innovation? Natural experimental evidence from China's anti‐corruption campaigns - Zhong, Weiguo; Zheng, Yanfeng (Strategic Management Journal, 2025)
Abstract Research Summary The impact of political connections on firm innovation remains unclear. Utilizing the unexpected removal of high‐ranking officials during China's anti‐corruption campaigns between 1999 and 2015 as an exogenous shock, we analyze this relationship to provide greater clarity. Employing a difference‐in‐differences approach, we find that firms that experience unexpected loss of political connections file significantly more patent applications than those that do not experience such disruption. Further analyses indicate that this innovation boost is more pronounced for firms operating in highly competitive markets and those with substantial knowledge stocks. Our research therefore contributes novel empirical evidence to the discourse on political connections and firm innovation, highlighting the inhibitory effect of political connections and offering insights into the political economy of innovation. Managerial Summary This study explores the impact of anti‐corruption campaigns on the innovation efforts of firms with political connections in China. We discover that when such firms experience the unexpected loss of their political connections, they tend to file more patent applications, although this does not necessarily result in more patents being granted. It is important for firms and policymakers to understand that the response to such losses is not uniform. Firms are more likely to enhance their innovation efforts through increased patent applications if they are facing intense market competition or possess a rich knowledge stock. These findings underscore the importance of fostering a competitive market environment alongside anti‐corruption campaigns to stimulate innovation. Our study therefore sheds light on how to precisely assess the impact of anti‐corruption campaigns on firm behaviors and strategies.